2006
DOI: 10.1371/journal.pgen.0020173
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Discordance of Gene Trees with Species Tree in Drosophila: Evidence for Incomplete Lineage Sorting

Abstract: The phylogenetic relationship of the now fully sequenced species Drosophila erecta and D. yakuba with respect to the D. melanogaster species complex has been a subject of controversy. All three possible groupings of the species have been reported in the past, though recent multi-gene studies suggest that D. erecta and D. yakuba are sister species. Using the whole genomes of each of these species as well as the four other fully sequenced species in the subgenus Sophophora, we set out to investigate the placemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
317
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(340 citation statements)
references
References 124 publications
18
317
1
Order By: Relevance
“…The greatest theoretical challenge posed by genetic introgression studies is proving that the observed pattern of shared alleles between species is the product of recent introgression, as opposed to noncontemporary process such as ancient introgression or the incomplete lineage sorting of genes after speciation (deep coalescence; Pollard et al, 2006;Willyard et al, 2009), as shown in Figure 1. The genetic signature of incomplete lineage sorting is the same as ancient introgression soon after speciation, so we treat these together, and contrast this with recent introgression (introgression here).…”
Section: Proving Introgression As Opposed To Incomplete Lineage Sortingmentioning
confidence: 99%
See 1 more Smart Citation
“…The greatest theoretical challenge posed by genetic introgression studies is proving that the observed pattern of shared alleles between species is the product of recent introgression, as opposed to noncontemporary process such as ancient introgression or the incomplete lineage sorting of genes after speciation (deep coalescence; Pollard et al, 2006;Willyard et al, 2009), as shown in Figure 1. The genetic signature of incomplete lineage sorting is the same as ancient introgression soon after speciation, so we treat these together, and contrast this with recent introgression (introgression here).…”
Section: Proving Introgression As Opposed To Incomplete Lineage Sortingmentioning
confidence: 99%
“…Empirical evidence is therefore required to infer introgression based on shared alleles between species (Slotte et al, 2008;Du et al, 2009). This is particularly a problem in species with a large effective population size (N e ), where high intraspecific allelic diversity makes inferences of hybridization difficult, or in recently speciating groups where levels of divergence are low (Pollard et al, 2006). This problem is illustrated by population studies in oaks (Quercus).…”
Section: Proving Introgression As Opposed To Incomplete Lineage Sortingmentioning
confidence: 99%
“…First, we do not consider incomplete lineage sorting (ILS) events, which may not be rare and hence cannot be ignored in certain circumstances [18,20]. Since the effect of an ILS event on the divergence of gene and species trees is similar to that of a duplication event, the concepts proposed here can easily be extended to take into account ILS.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Different topologies for different markers are often the result of ancestral polymorphism, incomplete lineage sorting or events of gene flow that occur during the speciation process (POLLARD et al 2006). Discrepancies between nuclear and mitochondrial DNA surveys may also be related to the higher mutation rate of mtDNA (JOHNSON et al 2003).…”
Section: Boroveci:b Rozneri)mentioning
confidence: 99%